Global Peripartum Mental Health: The Silent Burden for Women in Low- and Middle-Income Countries. Issue 6 (November 2022) - Callister, Lynn Clark
Abstract : Global maternal mental health issues are increasing in low- and middle-income countries as well as the United States. The COVID-19 pandemic has had a negative effect on maternal mental health. Our global health and nursing expert, Dr. Callister, summarizes some of the recently published evidence on global maternal mental health.